The aetiology and pathogenesis of squamous and basal cell carcinoma - Oliveira Soares, R. (1998)
Basal cell carcinoma (BCC) is the most frequently encountered human malignant tumour. Squamous cell carcinoma (SCC), also common, has a more aggressive biological behaviour. Ultraviolet radiation (UR) is the most important epidemiological carcinogenicfactor in the evolution of BCC and SCC. Low phototype patients have a higher incidence of these tumours, which occur, mainly in exposed areas. Childhood sun exposition could be important. The carcinogenic potential of UR is experimentally confirmed. Other kinds of radiation, chemical substances and viruses could also be implicated in the aetiopathogenesis. These associations are not yet fully understood. There does not seem to exista sole mechanism which causes a normally diffterentiated keratinocyte to transform into a malignant cell, with the po tentialfor local invasion and distant metastases. The way this change occurs still remains almost unknown.